“Percorsi nel Blu” (“Blue Paths”): a long-lasting project to integrate Ocean Literacy and Marine Citizen Science into school curricula - MIONI, ERIKA (Mediterranean Marine Science, 2022)
The “Percorsi nel Blu” project is a revolutionary “Blue School” model of well-integrated Ocean Literacy (OL) and Marine Citizen Science (MCS), promoted by a science teacher and independent researcher of the ISA2 secondary school institute of La Spezia, Italy. Since 2011 the Project has been setting up a network among schools, institutions, citizens, and a partnership with research centers for data collection activities within coastal sites located in the “Pelagos” Mammals’ Sanctuary, in the Ligurian and Tyrrhenian Seas. The project focuses on the key points of OL and MCS, promoting a gradual implementation of scientific literacy in marine biology and coastal monitoring techniques in school curricula during a period of vertical and incremental long-lasting training, from kindergarten up to university. “Percorsi nel Blu” harmonizes the existing educational plans with the last recommendations of the United Nations Sustainable Development Goals (UN SDGs) of the 2030 Agenda in order to improve the teaching of science, technology, engineering, and mathematics (STEM disciplines). The OL process follows the whole educational path, involving students more and more actively in the recognition of marine flora and fauna during research activities on the beach and scuba surveys in research campaigns. The great impact on the community, the remarkable number of participants, and the relevant scientific results of the first records of alien and native species increase students’ interest in STEM disciplines and marine science and encourage them to disseminate their experiences, thus creating the awareness of global citizenship which includes the whole community, both inside and outside school.